The Role of Environmental NGOs in Indonesia’s Policy on Re-Export Plastic Waste to Anticipate Non-Military Threats - Yordania Mega Priyanti; Herlina Juni Risma Saragih; Agung Risdhianto; Hikmat Zakky Almubaraq (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This paper analyzes an important gap in understanding the role of the Environmental Non-Government Organizations in Indonesia’s policy on re-export waste. This paper provides insights into how NGOs can be more effective to enforce Indonesia’s policy on re-export plastic waste to anticipate non-military threats and protect the environment and public health from the harmful effects of illegal waste imports. Moreover, this research will help to ensure that the government is held accountable for enforcing its policies regarding waste plastic import. Using the New social movement theory by Philip W. Sutton and the descriptive qualitative approach can answer and help to understand the role of Environmental NGOs. The result shows that Environmental NGOs played a significant role in shaping Indonesia’s on implementing re-export plastic waste and used various actions such as advocacy, lobbying, and awareness campaigns to influence policy decisions and ensure that the government’s policies were in line with environmental protection. The new social movement theory emphasizes the role of non-government organizations in shaping the social environment, especially in raising awareness of the environmental and health risks posed by plastic waste.